PENERAPAN PENERAPAN PERAGA MESIN DIESEL UNTUK MENINGKATKAN PEMAHAMAN KOMPONEN MESIN DIESEL PADA PRAKTIK MOTOR BENSIN DAN DIESEL - Susanto, Edi; Rahardjo, Winarno Dwi (Journal of Mechanical Engineering Learning, 2020)
The purpose of this study is to determine the feasibility of a diesel engine display and findout how much student learning outcomes (understanding) improve about diesel enginecomponents by using the visual aid. Based on the results of the product feasibility test itis obtained a percentage of 82% for media experts with a very decent category and 78%for material experts with a feasible category. Based on the results of the study, an increasein the average of pretest-posttest value is 23 or 40%, the t-test shows the value of t count= 14.89> t table = 2.02. The increase of student learning outcomes indicates an averageof the N-Gain test = 0.57 with the criteria of moderate improvement.Keywords: Learning outcomes, visuals aid, understanding, diesel engine